Sugar industry waste-derived anode for enhanced biohydrogen production from rice mill wastewater using artificial photo-assisted microbial electrolysis cell. (17th June 2021) - Keruthiga, Kaliaperumal; Mohamed, Samsudeen Naina; Gandhi, Nagarajan Nagendra; Muthukumar, Karuppan
Abstract: Microbial Electrolysis Cell (MEC) is a promising green technology for energy production from wastewater. This study attempts to investigate the biohydrogen production from rice mill wastewater using artificial photo-assisted microbial electrolysis cell (APAMEC) with an inexpensive anode prepared from carbonaceous material disposed by sugar industry. The X-ray diffraction (XRD) and scanning electron microscopic (SEM) analyses confirmed the presence of carbon on the electrode surface. Cyclic Voltammogram analysis indicated that the carbonaceous anode has higher reduction peak at 0.7 V compared to control (plain carbon cloth) electrode. The experimental results showed a maximum hydrogen production of 220 mL on 5th day of fermentation and the production rate observed was 3.6 ± 0.4 mL/l/h. The effect of pH and acid concentration used in the acid hydrolysis of rice mill wastewater and the effect of artificial light on biohydrogen production were investigated. The optimum pH and acid concentration of 6 and 1.5%, respectively, gave better biohydrogen production and COD removal. The results demonstrated that the development of inexpensive anode from the waste disposed by sugar industry would pave the path to scale-up MECs. Highlights: Biohydrogen production from rice mill wastewater using APAMEC was investigated. Inexpensive catalyst was prepared from the waste disposed by the sugar industry. Detailed characterization of electrodes was done. The maximum hydrogen production rate of 3.6 ± 0.4 mL/L/h was observed. The pH, acid concentration and light intensity influenced the biohydrogen production.